Design and Manufacturing of the Steering System in the KMHE Laksamana V 1.0 Prototype Vehicle - Istana, Budi; Aydil Hijerah Harahap; Sunaryo (Universitas Muhammadiyah Sidoarjo, 2025)
The Energy Efficient Car Contest (Kontes Mobil Hemat Energi or KMHE) is a national competition in Indonesia that challenges university students to develop ultra-efficient prototype vehicles. This study presents the design, simulation, and manufacturing of a custom steering system for the Laksamana V 1.0 single-passenger prototype vehicle developed by Team Laksamana. The steering system was engineered to meet strict requirements for weight, structural reliability, ergonomic fit, and maneuverability under competition conditions. A rack-and-pinion mechanism was selected after comparative evaluation of multiple steering concepts. Computer-Aided Design (CAD) and Finite Element Analysis (FEA) were employed to optimize the geometry and assess the mechanical strength of key components, including a tie rod made from SUS 201 stainless steel. The manufactured system weighs 3.74 kg, delivers a steering ratio of 12:1, and requires 2.8 Nm of torque, ensuring both agility and driver comfort. Although the measured turning radius was 6.3 meters—above the original target—it remains functional for KMHE circuits. FEA results confirmed that all structural stresses and deformations were well within safe limits, validating the design’s stiffness and durability. Overall, the developed steering system is reliable, efficient, and suitable for application in energy-efficient vehicle competitions.